Pendeteksi Propagasi Menggunakan Metode FM Berbasis Personal Komputer - Jamal, Zaidir (IIB Darmajaya, 2010)
Generally, point to point communication and broadcasting uses VHF band, each function VHF band can use for observes activities at ionosphere. This research designed and realized propagation detection use frequency modulation based personal computer. Results of the research are realization of system and simulation. Simulation results before ionosphere reflection occur is 50 % and after ionosphere reflection occur is 90 %. Frequency modulation method can be implemented earthquake detection with realized measurement stations. Keyword : VHF, Propagation, ionosphere